Ceruloplasmin, transferrin and apolipoprotein A-II play important role in treatment’s followup of paracoccidioidomycosis patients - Sylvestre, Tatiane Fernanda [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Silva, Julhiany de Fátima da [UNESP]; Paniago, Anamaria Mello Miranda; Weber, Simone Schneider; Pauletti, Bianca Alves; Carvalho, Lídia Raquel de [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Public Library of Science (PLoS), 2018)
Paracoccidioidomycosis (PCM) is a systemic disease caused by thermodymorphic fungi of the Paracoccidioides brasiliensis complex, (Paracoccidioides spp.). Patients with PCM reveal specific cellular immune impairment. Despite the effective treatment, quiescent fungi can lead to relapse, usually late, the serological diagnosis of which has been deficient. The present study was carried out with the objective of investigating a biomarker for the identification of PCM relapse and another molecule behaving as an immunological recovery biomarker; therefore, it may be used as a cure criterion. In the evolutionary analysis of the proteins identified in PCM patients, comparing those that presented with those that did not reveal relapse, 29 proteins were identified. The interactions observed between the proteins, using transferrin and haptoglobin, as the main binding protein, were strong with all the others. Patient follow-up suggests that cerulosplamin may be a marker of relapse and that transferrin and apolipoprotein A-II may contribute to the evaluation of the treatment efficacy and avoiding a premature decision.